Negative electrode active material, zinc ion battery and electronic device

By using a layered compound with the chemical formula AxBy as the negative electrode active material of the zinc ion battery, the dendrite, corrosion and passivation problems in the circulation of zinc ion batteries are solved, the cycle stability and safety of the battery are improved, and the cost is reduced.

CN115548287BInactive Publication Date: 2025-04-01WUHAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211125837.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing zinc ion batteries have dendrite, corrosion and passivation problems during the circulation process, resulting in extremely low utilization rate of zinc negative electrodes, high cost and poor safety.

Method used

A layered compound with the chemical formula AxBy is used as the negative electrode active material, where A is one or more of Ti, Cu, Mo, Fe, Bi, and B is one or more of S2-, Se2-, O2-, N3-, P3-, to prepare an aqueous zinc ion battery without zinc metal.

Benefits of technology

It improves the cycle stability of zinc ion batteries, avoids problems such as zinc dendrites, corrosion, and passivation, reduces the cost of the battery, enhances safety, and broadens the application areas of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115548287B_ABST
    Figure CN115548287B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode active material, a zinc ion battery and an electronic device. The chemical formula of the negative electrode active material of the present invention is A x B y The negative electrode active material is a layered compound. Compared with the existing zinc metal negative electrode, the negative electrode active material of the present application is used as the negative electrode. It has better cycle stability and will not cause zinc dendrites, corrosion, passivation and other problems, thereby improving the cycle performance of the battery. The zinc ion battery of the present invention uses the zinc-containing compound as the positive electrode and the layered compound as the negative electrode, and is used for aqueous zinc ion batteries that do not contain zinc metal, thereby broadening the application field of the material. The zinc ion battery of the present invention has the characteristics of safety, low cost, simple synthesis, long cycle life, no zinc dendrites, etc., and has good commercial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage, and in particular to a negative electrode active material, a zinc ion battery and an electronic device. Background Art

[0002] The excessive consumption of fossil fuels has led to increasingly serious problems of energy shortage and environmental degradation. Developing new energy is one of the effective strategies to solve the above problems. However, the generation of renewable energy such as solar energy, wind energy, tidal energy, geothermal energy, etc. is intermittent and volatile, and requires energy storage to smooth and stabilize the operation of the power system. Among the many energy storage technologies, electrochemical energy storage has the most outstanding comprehensive performance. As the most advanced electrochemical energy storage technology, lithium-ion batteries have achieved great success in the small electronic products and electric vehicle markets, but their application in the field of large-scale energy storage still needs to overcome the obstacles of high cost and poor safety.

[0003] Aqueous zinc-ion batteries have many advantages, such as high safety, abundant raw materials, low cost, and green environmental protection, and are one of the ideal choices for large-scale energy storage batteries. However, zinc metal anodes currently have problems such as dendrites, corrosion, and passivation. In addition, in order to meet the requirements of long cycles, the amount of zinc anode in the battery will far exceed the theoretical amount required, resulting in extremely low utilization of the zinc anode.

[0004] In view of the technical defects of current aqueous zinc-ion batteries, it is necessary to improve them. Summary of the invention

[0005] In view of this, the present invention provides a negative electrode active material, a zinc ion battery and an electronic device to solve or at least partially solve the technical problems existing in the prior art.

[0006] In a first aspect, the present invention provides a negative electrode active material, the chemical formula of the negative electrode active material is A x B y , wherein A is one or more of Ti, Cu, Mo, Fe, and Bi, and B is S 2- , Se 2- , O 2- , N 3- , P 3- One or more of <x≤3,0<y≤8。

[0007] In a second aspect, the present invention further provides a zinc ion battery, comprising a negative electrode, wherein the negative electrode comprises the negative electrode active material.

[0008] Preferably, the zinc ion battery further comprises a positive electrode, a separator and an electrolyte, wherein the positive electrode comprises a positive electrode active material, and the chemical formula of the positive electrode active material is Zn a M b Nc , where M is one or more of V, Mn, Fe, Cr, Co, Ni, Zr, Nb, Mo, and N is PO4 3- , P2O7 4- , SO4 2- , F - , O 2- One or more of <a≤3,0<b≤5,0<c≤5。

[0009] Preferably, in the zinc ion battery, the positive electrode and the negative electrode further include a conductive agent and a binder;

[0010] Wherein, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode is (5-9.5):(0.3-3):(0.2-2);

[0011] The mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode is (5-9.5):(0.3-3):(0.2-2).

[0012] Preferably, in the zinc ion battery, the electrolyte is a liquid or gel material with ionic conductivity and a soluble zinc salt as solute and water as solvent.

[0013] Preferably, in the zinc ion battery, the soluble zinc salt includes one or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, zinc chloride, zinc perchlorate, zinc nitrate, bis(fluorosulfonyl)imide zinc, and bis(trifluoromethanesulfonyl)imide zinc.

[0014] Preferably, in the zinc ion battery, the diaphragm comprises one of non-woven fabric, glass fiber, porous PP / PE diaphragm, PTFE membrane and glass fiber filter paper.

[0015] Preferably, in the zinc ion battery, the conductive agent includes one or more of graphite, carbon black, Ketjen black, carbon nanotubes, and graphene.

[0016] Preferably, in the zinc ion battery, the adhesive includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, polyacrylic acid, polyvinyl alcohol, and styrene-butadiene latex.

[0017] In a third aspect, the present invention further provides an electronic device comprising the zinc ion battery.

[0018] The negative electrode active material and zinc ion battery of the present invention have the following beneficial effects compared with the prior art:

[0019] 1. The chemical formula of the negative electrode active material of the present invention is A x B yThe negative electrode active material is a layered compound. Compared with the existing zinc metal negative electrode, the negative electrode active material of the present application is used as the negative electrode. It has better cycle stability and will not cause zinc dendrites, corrosion, passivation and other problems, thereby improving the cycle performance of the battery;

[0020] 2. The zinc ion battery of the present invention uses a zinc-containing compound as a positive electrode and a layered compound as a negative electrode, and is used for an aqueous zinc ion battery that does not contain zinc metal, thereby broadening the application field of the material; the zinc ion battery of the present invention has the characteristics of safety, low cost, simple synthesis, long cycle life, and no zinc dendrites, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 This is a scanning electron microscope image of the positive electrode active material Zn3V4(PO4)3 prepared in Example 1 of the present invention;

[0023] Figure 2 This is the XRD pattern of the positive electrode active material Zn3V4(PO4)3 prepared in Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the negative electrode active material TiS2 prepared in Example 1 of the present invention;

[0025] Figure 4 The XRD diagram of the positive electrode active material TiS2 prepared in Example 1 of the present invention;

[0026] Figure 5 The charge and discharge curve of the zinc ion battery prepared in Example 1 of the present invention is shown;

[0027] Figure 6 The positive electrode active material Zn prepared in Example 2 of the present invention 0.5 XRD pattern of VOPO4;

[0028] Figure 7 is the XRD pattern of the negative electrode active material TiSe2 prepared in Example 2 of the present invention;

[0029] Figure 8 The charge and discharge curve diagram of the zinc ion battery prepared in Example 2 of the present invention;

[0030] Fig. 9 This is the XRD pattern of the positive electrode active material Zn3V3O8 prepared in Example 3 of the present invention;

[0031] Fig.10 The negative electrode active material Cu prepared in Example 4 of the present invention 2-x Scanning electron micrograph of Se;

[0032] Fig.11 The negative electrode active material Cu prepared in Example 4 of the present invention 2-x XRD pattern of Se;

[0033] Fig.12 The figure is a cycle curve diagram of the zinc ion battery prepared in Example 1 of the present invention at a current density of 1C;

[0034] Fig.13 The figure is a charge and discharge curve diagram of the zinc ion battery prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0035] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0038] The present invention provides a negative electrode active material having a chemical formula of A x B y , wherein A is one or more of Ti, Cu, Mo, Fe, and Bi, and B is S 2- , Se 2- , O2- , N 3- , P 3- One or more of <x≤3,0<y≤8。

[0039] It should be noted that the chemical formula of the negative electrode active material of the present application is A x B y The negative electrode active material is a layered compound. Specifically, the negative electrode active material can be a layered compound such as titanium disulfide, titanium diselenide, molybdenum disulfide, copper sulfide selenide, etc. that stores zinc ions. Compared with the existing zinc metal negative electrode, the negative electrode active material of the present application is used as the negative electrode, which has better cycle stability and will not cause zinc dendrites, corrosion, passivation and other problems, thereby improving the cycle performance of the battery.

[0040] Based on the same inventive concept, an embodiment of the present application also provides a zinc ion battery, including a negative electrode, which includes the above-mentioned negative electrode active material.

[0041] In some embodiments, the zinc ion battery further comprises a positive electrode, a separator and an electrolyte, wherein the positive electrode comprises a positive electrode active material, wherein the chemical formula of the positive electrode active material is Zn a M b N c , where M is one or more of V, Mn, Fe, Cr, Co, Ni, Zr, Nb, Mo, and N is PO4 3- , P2O7 4- , SO4 2- , F - , O 2- One or more of <a≤3,0<b≤5,0<c≤5。

[0042] Specifically, in the above embodiment, the chemical formula of the positive electrode active material is Zn a M b N c , which is a polyanionic or oxide-type zinc-containing compound, which can provide a zinc source and match the non-zinc metal negative electrode; specifically, the positive electrode active material can adopt zinc-containing materials such as zinc vanadium phosphate, zinc vanadium fluorophosphate, zinc vanadium phosphate, zinc vanadate, zinc manganate, etc. that can reversibly release and embed zinc ions.

[0043] In some embodiments, the positive electrode and the negative electrode further include a conductive agent and a binder;

[0044] Wherein, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode is (5-9.5):(0.3-3):(0.2-2);

[0045] The mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode is (5-9.5):(0.3-3):(0.2-2).

[0046] Specifically, the preparation method of the positive electrode is: the positive electrode active material, the conductive agent and the binder are mixed and then coated on the positive electrode current collector; the preparation method of the negative electrode is: the negative electrode active material, the conductive agent and the binder are mixed and then coated on the negative electrode current collector. The positive electrode current collector and the negative electrode current collector include one of various metal foils, metal meshes, carbon cloths, graphite foils or graphite sheets.

[0047] In some embodiments, the electrolyte is a liquid or gel material with ionic conductivity and a soluble zinc salt as solute and water as solvent.

[0048] In some embodiments, the soluble salt of zinc includes one or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, zinc chloride, zinc perchlorate, zinc nitrate, zinc bis(fluorosulfonyl)imide, and zinc bis(trifluoromethanesulfonyl)imide.

[0049] In some embodiments, the separator includes one of non-woven fabric, glass fiber, porous PP / PE separator, PTFE membrane and glass fiber filter paper.

[0050] In some embodiments, the conductive agent includes one or more of graphite, carbon black, Ketjen black, carbon nanotubes, and graphene.

[0051] In some embodiments, the adhesive includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, polyacrylic acid, polyvinyl alcohol, and styrene-butadiene latex.

[0052] The zinc ion battery of the present application uses a zinc-containing compound as a positive electrode and a layered compound as a negative electrode, and is used for an aqueous zinc ion battery that does not contain zinc metal, thereby broadening the application field of the material; the zinc ion battery of the present application has the characteristics of safety, low cost, simple synthesis, long cycle life, and no zinc dendrites, and has good commercial prospects.

[0053] Based on the same inventive concept, the embodiment of the present application also provides an electronic device, including the above-mentioned zinc ion battery. Specifically, the electronic device can be an electronic device that uses a zinc ion battery as an operating power source to perform various functions (for example, playing music); the electronic device can also be an electronic terminal device such as a mobile phone, a tablet computer, a capacitor, a power bank, etc.; the electronic device can also be an electric tool that uses a zinc ion battery as a driving power source to move parts (for example, a drill); the electronic device also includes an electric vehicle that relies on a zinc ion battery as a driving power source, and can be a car equipped with other driving sources in addition to a zinc ion battery (including a hybrid vehicle).

[0054] The negative electrode active material and zinc ion battery of the present application are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0055] Example 1

[0056] The present application embodiment provides a positive electrode active material, whose chemical formula is Zn3V4(PO4)6, and the preparation method of the positive electrode active material is:

[0057] NH4VO3, NH4H2PO4, Zn(NO3)2, oxalic acid dihydrate, citric acid monohydrate and graphene are used as raw materials; wherein NH4H2PO4 is a phosphorus source, Zn(NO3)2 is a zinc source, and oxalic acid dihydrate, citric acid monohydrate and graphene are carbon sources;

[0058] 0.986 g NH4VO3 and 2.016 g oxalic acid dihydrate were added to 200 mL water, and dispersed for 3 h under magnetic stirring to obtain a solution; 1.38 g NH4H2PO4, 1.317 g Zn(NO3)2, 0.6 g citric acid monohydrate, and 0.1 g graphene were added to the above solution, and dispersed for 3 h under magnetic stirring, and then spray-dried at an air inlet rate of 80%, an air inlet temperature of 160°C, and a feed rate of 0.5% to obtain a precursor;

[0059] Then the precursor is placed in an argon atmosphere and calcined at 750°C for 12 hours to obtain Zn3V4(PO4)6.

[0060] The present application also provides a negative electrode active material, whose chemical formula is TiS2, and the preparation method of the negative electrode active material is:

[0061] Ti powder, S powder and graphene are used as raw materials; Ti powder is a titanium source, S powder is a sulfur source, and graphene is a carbon source.

[0062] 0.4787g Ti powder, 0.6414g S powder, and 0.0347g graphene were placed in a ball mill and ground for 1h. The ground powder was transferred to a borosilicate glass tube with one end open, and the other end was connected to a vacuum pump. The tube was sealed with an isobutane flame while evacuating. The sealed tube was then placed in a muffle furnace, heated to 550℃ at room temperature for 5h and calcined for 72h, cooled to room temperature, and washed several times with CS2 and C2H5OH to obtain TiS2.

[0063] The present application also provides an aqueous zinc ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator;

[0064] The preparation method of the positive electrode is as follows: Zn3V4(PO4)6 positive electrode active material, conductive agent and binder are weighed in a weight ratio of 80:10:10, wherein the conductive agent is conductive carbon black SP and the binder is 60% PTFE emulsion; firstly, the Zn3V4(PO4)6 positive electrode active material and the conductive carbon black SP are evenly ground in an agate mortar to obtain a powder material for standby use; then the binder PTFE emulsion is placed in a beaker, isopropyl alcohol is added to break the emulsion, and then the ground powder material is added, the slurry is adjusted and dried under an infrared lamp, and finally the membrane is rolled into a film on a roller machine, the membrane is placed in a vacuum oven at 80°C for more than 6 hours, and pressed on a stainless steel mesh to obtain a positive electrode;

[0065] The preparation method of the negative electrode is as follows: TiS2 negative electrode active material, conductive agent and binder are weighed in a weight ratio of 80:10:10, wherein the conductive agent is conductive carbon black SP and the binder is 60% PTFE emulsion; firstly, the TiS2 negative electrode active material and the conductive carbon black SP are evenly ground in an agate mortar to obtain a powder material for standby use; then the binder PTFE emulsion is put into a beaker, isopropyl alcohol is added to break the emulsion, and then the ground powder material is added, the slurry is adjusted and dried under an infrared lamp, and finally the membrane is rolled into a film on a roller machine, the membrane is put into a vacuum oven at 80°C for more than 6 hours, and pressed on a stainless steel mesh to obtain the negative electrode;

[0066] The electrolyte is 3 mol·L -1 of an aqueous solution of zinc trifluoromethanesulfonate.

[0067] The diaphragm is glass fiber.

[0068] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a button-type aqueous zinc-ion battery.

[0069] Example 2

[0070] The present invention provides a positive electrode active material, the chemical formula of which is Zn 0.5 VOPO4, the preparation method of the positive electrode active material is:

[0071] H3PO4, HNO3, V2O5, ZnI2 and ethylene glycol dimethyl ether are used as raw materials; wherein H3PO4 is a phosphorus source, V2O5 is a vanadium source, ZnI2 is a zinc source, HNO3 is an oxidant, and ethylene glycol dimethyl ether is a solvent;

[0072] 2.4 g of V2O5, 13.3 mL of H3PO4, and 10 mL of HNO3 were added to 55.7 mL of water, and reacted in an oil bath at 110°C for 16 h under magnetic stirring. After cooling, the mixture was filtered, washed three times with acetone and water respectively, and dried in a vacuum drying oven at 80°C for 12 h to obtain VOPO4·2H2O. 0.5 g of the prepared VOPO4·2H2O, 4.625 g of ZnI2, and 20 mL of ethylene glycol dimethyl ether were added to a 100 mL hydrothermal reactor and reacted at 140°C for 10 h. After cooling, the mixture was filtered, washed three times with ethylene glycol dimethyl ether, and dried in a vacuum drying oven at 80°C for 12 h to obtain Zn 0.5 VOPO4.

[0073] The present application also provides a negative electrode active material, whose chemical formula is TiSe2, and the preparation method of the negative electrode active material is:

[0074] Ti powder, Se powder and graphene are used as raw materials; Ti powder is a titanium source, Se powder is a selenium source, and graphene is a carbon source.

[0075] 0.2393g Ti powder and 0.7896g Se powder were placed in a mortar and ground to mix evenly; the mixed powder was transferred to a high borosilicate glass tube with one end open, and the other end was connected to a vacuum pump, and the tube was sealed with an isobutane flame while evacuating. Then the sealed tube was placed in a muffle furnace, heated to 450℃ at room temperature for 4h, calcined for 72h, cooled to room temperature, and washed several times with ethylenediamine and C2H5OH to obtain TiSe2.

[0076] The present application also provides an aqueous zinc ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator;

[0077] The preparation method of the positive electrode is as follows: Zn is weighed in a weight ratio of 50:30:20. 0.5 VOPO4 positive electrode active material, conductive agent, binder, wherein the conductive agent is graphite, and the binder is a 2% by weight sodium carboxymethyl cellulose solution; firstly, Zn 0.5 The VOPO4 positive electrode active material and graphite are evenly ground in an agate mortar to obtain a powder material for later use; then the sodium carboxymethyl cellulose solution is placed in a beaker, isopropyl alcohol is added to break the emulsion, and then the ground powder material is added, the slurry is adjusted and dried under an infrared lamp, and finally the film is rolled into a film on a roller mill, and the film is placed in a vacuum oven at 100°C for more than 6 hours, and pressed on a titanium mesh to obtain a positive electrode;

[0078] The preparation method of the negative electrode is as follows: TiSe2 negative electrode active material, conductive agent and binder are weighed in a weight ratio of 50:30:20, wherein the conductive agent is graphite and the binder is a sodium carboxymethyl cellulose solution with a weight percentage of 2%; firstly, the TiSe2 negative electrode active material and graphite are evenly ground in an agate mortar to obtain a powder material for standby use; then the sodium carboxymethyl cellulose solution is put into a beaker, isopropyl alcohol is added to break the emulsion, and then the ground powder material is added, the slurry is adjusted and dried under an infrared lamp, and finally the diaphragm is rolled into a film on a roller machine, the diaphragm is put into a vacuum oven at 100°C for more than 6 hours, and pressed on a titanium mesh to obtain the negative electrode;

[0079] The electrolyte contains 1 mol·L -1 of zinc sulfate and 0.5 mol·L -1 of an aqueous solution of glucose;

[0080] The diaphragm is glass fiber;

[0081] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a button-type aqueous zinc ion battery.

[0082] Example 3

[0083] The present application embodiment provides a positive electrode active material, whose chemical formula is Zn3V3O8, and the preparation method of the positive electrode active material is:

[0084] Zn(COOCH3)2·2H2O, V2O5 and citric acid are used as raw materials; wherein Zn(COOCH3)2·2H2O is a zinc source, V2O5 is a vanadium source, and citric acid is a carbon source;

[0085] 1.0975g Zn(COOCH3)2·2H2O, 0.906g V2O5 and 0.6g monohydrate citric acid were added to a ball mill and mixed evenly with acetone, and stirred at 300r / min for 6h to fully mix the materials; then the stirred materials were taken out and placed in a drying oven at 80°C for 12h to obtain a precursor; the precursor was placed in an argon atmosphere, calcined at 500°C for 3h, and then raised to 800°C for 8h to obtain Zn3V3O8;

[0086] The present application also provides an aqueous zinc ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator;

[0087] The preparation method of the positive electrode is as follows: Zn3V3O8 positive electrode active material, conductive agent and binder are weighed in a weight ratio of 95:3:2, wherein the conductive agent is carbon nanotubes and the binder is sodium alginate emulsion; firstly, the Zn3V3O8 positive electrode active material and the carbon nanotubes are evenly ground in an agate mortar to obtain a powder material for standby use; then, the binder sodium alginate emulsion is put into a beaker, and then the ground powder material is added, slurry is adjusted and dried under an infrared lamp, and finally, the film is rolled into a film on a roller machine, and the film is placed in a vacuum oven at 100°C for more than 6 hours, and pressed on a titanium foil to obtain a positive electrode;

[0088] The preparation method of the negative electrode is as follows: weigh TiS2 negative electrode active material (preparation method is the same as in Example 1), conductive agent, and binder in a weight ratio of 95:3:2, wherein the conductive agent is carbon nanotubes and the binder is sodium alginate emulsion; firstly grind the TiS2 negative electrode active material and the carbon nanotubes in an agate mortar evenly to obtain a powder material for standby use; then take the binder sodium alginate emulsion and put it in a beaker, then add the ground powder material, slurry mix and dry under an infrared lamp, and finally roll it into a film on a roller mill, put the film into a vacuum oven at 100°C for more than 6 hours, and press it on a titanium foil to obtain the negative electrode;

[0089] The electrolyte contains 2 mol·L -1 of zinc nitrate and 0.5 mol·L -1 An aqueous solution of ammonium acetate;

[0090] The diaphragm is a porous PP diaphragm;

[0091] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a square aqueous solution zinc ion battery.

[0092] Example 4

[0093] The present application also provides a negative electrode active material, the chemical formula of which is Cu 2-x Se, the preparation method of the negative electrode active material is:

[0094] Cu(COOCH3)2·H2O (copper acetate monohydrate), Na2SeO3 (sodium selenite) and C2H8N2 (ethylenediamine) are used as raw materials; wherein, Cu(COOCH3)2·H2O is a copper source, Na2SeO3 is a selenium source, and C2H8N2 is a reducing agent for high-valent selenium.

[0095] Cu with starfish morphology was prepared by a one-step hydrothermal method. 2-xSe, specifically: add 0.8g Cu(COOCH3)2·H2O, 0.346g Na2SeO3, and 3mL C2H8N2 to 22mL deionized water, stir vigorously for 30min, and fully mix and dissolve to obtain a mixed solution; transfer the mixed solution to a 100mL Teflon-lined stainless steel reactor and keep it at 180℃ for 24h; wash the black precipitate at the bottom of the reactor with deionized water and anhydrous ethanol for multiple times and centrifuge, then dry it in vacuum at 60℃ to obtain Cu 2-x Se.

[0096] The present application also provides an aqueous zinc ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator;

[0097] The preparation method of the positive electrode is as follows: Zn and 0.5 VOPO4 positive electrode active material (preparation method is the same as in Example 2), conductive agent, binder, wherein the conductive agent is graphene, and the binder is polyacrylic acid emulsion; firstly, Zn 0.5 The VOPO4 positive electrode active material and graphene are evenly ground in an agate mortar to obtain a powder material for later use; then the polyacrylic acid emulsion is placed in a beaker, and then the ground powder material is added, and the slurry is adjusted under an infrared lamp, and finally the graphite sheet is dipped, and the graphite sheet containing the active material is placed in a vacuum oven at 100°C for more than 6 hours to obtain the positive electrode;

[0098] The preparation method of the negative electrode is as follows: Cu and 2-nitropropene are weighed in a weight ratio of 60:20:20. 2-x Se negative electrode active material, conductive agent, binder, wherein the conductive agent is graphene, and the binder is polyacrylic acid emulsion; firstly, Cu 2-x Se negative electrode active material and graphene are ground evenly in an agate mortar to obtain powder material for later use; polyacrylic acid emulsion is then placed in a beaker, followed by adding the ground powder material, slurrying is performed under an infrared lamp, and finally, the powder material is dipped on a graphite sheet, and the graphite sheet containing the active material is placed in a vacuum oven at 100°C for more than 6 hours to obtain a negative electrode;

[0099] The electrolyte is a polyacrylamide hydrogel electrolyte containing ZnSO4, and the preparation method thereof is as follows: the synthesized polyacrylamide hydrogel is immersed in 1 mol·L -1 After 24 hours in ZnSO4 solution, the polyacrylamide hydrogel electrolyte containing ZnSO4 was obtained;

[0100] The diaphragm is filter paper;

[0101] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a soft-pack aqueous zinc ion battery.

[0102] Example 5

[0103] The embodiment of the present application provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator;

[0104] The preparation method of the positive electrode is as follows: weigh Zn3V4(PO4)6 positive electrode active material (the preparation method is the same as in Example 1), a conductive agent, and a binder in a weight ratio of 70:20:10, wherein the conductive agent is acetylene black and the binder is a 2% sodium carboxymethyl cellulose solution; first grind the Zn3V4(PO4)6 positive electrode active material and acetylene black in an agate mortar to obtain a powder material for standby use; then put the sodium carboxymethyl cellulose solution in a beaker, then add the ground powder material, slurry it under an infrared lamp, and finally dip it on a carbon cloth, put the carbon cloth containing the active material into a 100°C vacuum oven for more than 6 hours, and obtain the positive electrode;

[0105] The preparation method of the negative electrode is as follows: Cu and Mg are weighed in a weight ratio of 70:20:10. 2-x Se negative electrode active material (preparation method is the same as in Example 4), conductive agent, binder, wherein the conductive agent is acetylene black, and the binder is 2% sodium carboxymethyl cellulose solution; first, Cu 2-x Se negative electrode active material and acetylene black are ground evenly in an agate mortar to obtain a powder material for later use; then a sodium carboxymethyl cellulose solution is placed in a beaker, and then the ground powder material is added, and the slurry is adjusted under an infrared lamp, and finally a spot is dipped on a carbon cloth, and the carbon cloth containing the active material is placed in a vacuum oven at 100°C for more than 6 hours to obtain a negative electrode;

[0106] The electrolyte contains 3 mol·L -1 of zinc trifluoromethanesulfonate and 0.5 mol·L -1 An aqueous solution of potassium dihydrogen phosphate;

[0107] The diaphragm is glass fiber;

[0108] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a button-type aqueous zinc ion battery.

[0109] Comparative Example 1

[0110] This comparative example provides an aqueous zinc ion battery, including a positive electrode, a negative electrode, an electrolyte and a separator;

[0111] Wherein, the preparation method of the positive electrode is the same as that of Example 1;

[0112] The negative electrode active material is zinc powder; the preparation method of the negative electrode is as follows: the zinc powder negative electrode active material, the conductive agent and the binder are weighed in a weight ratio of 80:10:10, wherein the conductive agent is conductive carbon black SP, and the binder is 60% by weight of PTFE emulsion; firstly, the zinc powder negative electrode active material and the conductive carbon black SP are evenly ground in an agate mortar to obtain a powder material for standby use; then, the binder PTFE emulsion is put into a beaker, isopropyl alcohol is added to break the emulsion, and then the ground powder material is added, the slurry is adjusted and dried under an infrared lamp, and finally, the diaphragm is rolled into a film on a roller machine, the film is placed in a vacuum oven at 80° C. for more than 6 hours, and pressed on a titanium mesh to obtain the negative electrode; the utilization rate of the zinc negative electrode in this comparative example is 20%;

[0113] The electrolyte is 3 mol·L -1 An aqueous solution of zinc trifluoromethanesulfonate;

[0114] The diaphragm is glass fiber;

[0115] The positive electrode, the negative electrode, the electrolyte and the separator are assembled into a button-type aqueous zinc ion battery.

[0116] Performance Testing

[0117] The surface morphology and X-ray diffraction of the positive electrode active material Zn3V4(PO4)6 prepared in Example 1 were tested. The results are as follows: Figure 1 , Figure 2 As shown, from Figures 1-2 It can be seen that the positive electrode active material Zn3V4(PO4)6 is spherical with uniform size, and the size is approximately between 1 and 4 μm.

[0118] The surface morphology and X-ray diffraction of the negative electrode active material TiS2 prepared in Example 1 were tested. The results are as follows: Figure 3 , Figure 4 As shown, from Figures 3-4 It can be seen that the negative electrode active material TiS2 is a pure compound, all peaks are consistent with the TiS2 structure (JCPDS No. 70-6204), the morphology is flaky, coated with graphene, and the size is approximately between 3 and 8 μm.

[0119] The aqueous zinc ion battery assembled in Example 1 was subjected to charge and discharge tests. The results are as follows: Figure 5 As shown, the constant current charge and discharge mode is used for testing, the charge cut-off voltage is 1.6V, and the discharge cut-off voltage is 0.1V. Figure 5 It can be seen that the zinc ion discharge capacity of this example can reach 94.6 mAh g -1 .

[0120] The positive electrode active material Zn prepared in Example 2 was tested 0.5 The X-ray diffraction results of VOPO4 are as follows Figure 6 As shown, from Figure 6 It can be seen that the positive electrode active material Zn 0.5 The characteristic peaks of VOPO4 and VOPO4·2H2O structure (JCPDS No. 84-0111) have a more obvious shift, which proves the embedding of Zn.

[0121] The surface morphology and X-ray diffraction of the negative electrode active material TiSe2 prepared in Example 2 were tested. The results are as follows: Figure 7 As shown, from Figure 7 It can be seen that the negative electrode active material TiSe2 is a pure compound, and all peaks are consistent with the TiSe2 structure (JCPDS No. 65-2037).

[0122] The aqueous solution zinc ion battery assembled in Example 2 was charged and discharged using a constant current charge and discharge mode. The results are as follows: Figure 8 As shown, the constant current charge and discharge mode is used for testing, the charge cut-off voltage is 1.6V, and the discharge cut-off voltage is 0.1V; Figure 8 It can be seen that the zinc ion discharge capacity of this example can reach 107 mAh g -1 .

[0123] The X-ray diffraction of the positive electrode active material Zn3V3O8 prepared in Example 3 was tested, and the results were as follows: Fig. 9 As shown, from Fig. 9 It can be seen that the positive electrode active material Zn3V3O8 is a pure compound.

[0124] The negative electrode active material Cu prepared in Example 4 was tested 2-x The surface morphology and X-ray diffraction of Se are shown in Figure 2. Fig.10 , Fig.11 As shown, from Figures 10-11 It can be seen that the negative electrode active material Cu 2-x Se is a pure compound, and all peaks are related to Cu 2-x Se structure (JCPDS No. 06-0680), the morphology is starfish-shaped, and the size is approximately between 3 and 6 μm.

[0125] The cycle curve of the aqueous zinc ion battery assembled in Example 1 at 1C current density was tested, and the results were as follows: Fig.12 As shown, from Fig.12 It can be seen that the initial capacity of the zinc ion battery obtained in this example is 94.6 mAh·g at a current density of 1C. -1 , the capacity retention rate after 100 cycles is 94.3%, which has good performance.

[0126] The aqueous zinc ion battery assembled in Comparative Example 1 was subjected to charge and discharge tests. The results are as follows: Fig.13 As shown, the constant current charge and discharge mode is used for testing, the charge cut-off voltage is 1.9V, and the discharge cut-off voltage is 0.3V. Fig.13 It can be seen that the zinc ion discharge capacity of this comparative example is 37.1 mAh g -1 After 3 weeks of cycling, the capacity is only 16 mAh g -1 The reversible capacity and cycle performance are much lower than those of the battery in Example 1.

[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A zinc ion battery, characterized in that: Including positive electrode, negative electrode, electrolyte and separator; The positive electrode includes Zn in a weight ratio of 50:30:20 0.5 VOPO4 positive electrode active material, conductive agent, binder, wherein the conductive agent is graphite, and the binder is 2% by weight sodium carboxymethyl cellulose solution; The negative electrode includes a TiSe2 negative electrode active material, a conductive agent, and a binder in a weight ratio of 50:30:20, wherein the conductive agent is graphite and the binder is a sodium carboxymethyl cellulose solution with a weight percentage of 2%; The electrolyte contains 1 mol·L −1 of zinc sulfate and 0.5 mol·L −1 of an aqueous solution of glucose; Zn 0.5 The preparation method of VOPO4 positive electrode active material is: 2.4 g V2O5, 13.3 mL H3PO4, and 10 mL HNO3 were added to 55.7 mL water, and reacted in an oil bath at 110°C for 16 h under magnetic stirring. After cooling, the mixture was filtered, washed three times with acetone and water respectively, and dried in a vacuum drying oven at 80°C for 12 h to obtain VOPO4·2H2O. 0.5 g of the prepared VOPO4·2H2O, 4.625 g ZnI2, and 20 mL ethylene glycol dimethyl ether were added to a 100 mL hydrothermal reactor and reacted at 140°C for 10 h. After cooling, the mixture was filtered, washed three times with ethylene glycol dimethyl ether, and dried in a vacuum drying oven at 80°C for 12 h to obtain Zn 0.5 VOPO4; The diaphragm is fiberglass.

2. An electronic device, characterized in that: Comprising the zinc ion battery as claimed in claim 1.

Citation Information

Patent Citations

  • Rechargeable zinc metal battery

    US20230018070A1